2016
DOI: 10.1039/c5en00187k
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of evidence for silver nanoparticle-induced mitochondrial toxicity

Abstract: Here we review mitochondrial effects of silver nanoparticle (AgNP) exposure, which may mediate overall cytotoxicity observed following AgNP exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 110 publications
2
76
0
Order By: Relevance
“…The Ag-NPs cause significant genotoxicity and cytotoxicity due to oxidative stress and inflammation (Asharani et al 2009;Ivask et al 2015;Maurer and Meyer 2016). Evidence of published literature suggested that Ag-NPs induce damage to DNA due to double strands breaks, fragmentation and fusions (AshaRani et al 2008;Kovvuru et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The Ag-NPs cause significant genotoxicity and cytotoxicity due to oxidative stress and inflammation (Asharani et al 2009;Ivask et al 2015;Maurer and Meyer 2016). Evidence of published literature suggested that Ag-NPs induce damage to DNA due to double strands breaks, fragmentation and fusions (AshaRani et al 2008;Kovvuru et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There are several review papers published to address the issues associated with AgNPs in terms of their toxicology properties during their use as antimicrobial agents for textiles, dental biomaterials, and bio‐detectors, as well as during their syntheses . For instance, toxicity properties including cytotoxicity and genotoxicity of capped or uncapped AgNPs have been reviewed in detail .…”
Section: Introductionmentioning
confidence: 99%
“…The reviews published so far on nanoparticle toxicology provide information about toxicity of engineered nanoparticles to environmental microorganisms [20], titanium oxide nanoparticle toxicity [21], gold nanoparticle toxicity [21], risk management of inhaled nanoparticles [22], induced mitochondrial toxicity of silver nanoparticles [23] and single-wall carbon nanotube toxicity [24] and multi-wall carbon nanotube toxicity [25]. The published reviews are either too general or very specific (focusing on a single nanoparticle or toxicological effects on a particular organ) to explain the toxicity.…”
Section: Introductionmentioning
confidence: 99%